The translation‐to‐policy learning cycle to improve public health - Amy M. Kilbourne; Melissa Z. Braganza; Dawn M. Bravata; Jack Tsai; Richard E. Nelson; Alex Meredith; Kenute Myrie; Rachel Ramoni (Wiley, 2024)
Abstract Objective Learning Health Systems (LHSs) have not directly informed evidence‐based policymaking. The Translation‐to‐Policy (T2P) Learning Cycle aligns scientists, end‐users, and policymakers to support a repeatable roadmap of innovation and quality improvement to optimize effective policies toward a common public health goal. We describe T2P learning cycle components and provide examples of their application. Methods The T2P Learning Cycle is based on the U.S. Department of Veterans Affairs (VA) Office of Research and Development and Quality Enhancement Research Initiative (QUERI), which supports research and quality improvement addressing national public health priorities to inform policy and ensure programs are evidence‐based and work for end‐users. Incorporating LHS infrastructure, the T2P Learning Cycle is responsive to the Foundations for Evidence‐based Policymaking Act, which requires U.S. government agencies to justify budgets using evidence. Results The learning community (patients, providers, clinical/policy leaders, and investigators) drives the T2P Learning Cycle, working toward one or more specific, shared priority goals, and supports a repeatable cycle of evidence‐building and evaluation. Core T2P Learning Cycle functions observed in the examples from housing/economic security, precision oncology, and aging include governance and standard operating procedures to promote effective priority‐setting; complementary research and quality improvement initiatives, which inform ongoing data curation at the learning system level; and sustainment of continuous improvement and evidence‐based policymaking. Conclusions The T2P Learning Cycle integrates research translation with evidence‐based policymaking, ensuring that scientific innovations address public health priorities and serve end‐users through a repeatable process of research and quality improvement that ensures policies are scientifically based, effective, and sustainable.